The impact of educational achievement on the integration and wellbeing of Afghan refugee youth in the UK - Catherine Gladwell; Jennie Thomas; Georgina Chetwynd; Saliha Majeed; Carolyn Burke; Victoria Stubbs; Seemin Zahid (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Unprecedented numbers of unaccompanied asylum-seeking children have arrived in Europe over the last decade, and young Afghans account for the highest proportion of unaccompanied asylum-seeking children across the UK. Despite research exploring the experiences of child refugees and asylum seekers, less is documented about the experiences of former unaccompanied minors after the age of 18. Using practice-based research, we draw on three new primary data sources to examine factors facilitating and impeding the socioeconomic integration and wellbeing of Afghan former unaccompanied minors. We demonstrate the role of education in creating socioeconomic opportunities, and show how unresolved immigration status detracts from wellbeing.
Keywords: I24; I26; I31; J60; Z18; 330; migration; refugees; youth; Afghans; education; qualitative research